Impact of lameness on production, reproduction and health of dairy cows - Suarez, Victor Humberto; Martinez, Gabriela Marcela; Wirsh, S. (Ediciones INTA, 2025)
In order to investigate the consequences of lameness on dairy cattle productive, reproductive efficiency, and health, records from the software of 6 dairy farms located in central Argentina were studied. Two randomly chosen cow groups were compared: lame group (LG; n= 510) and healthy control group without lameness (CG; n= 510). Milk liters at 305 days (L/305), total milk liters (TL), days in milk (DIM), open days (OD) insemination number (IN), calving intervals (CI), health disorders and culled or death cows were recorded. Parameters were taken in the initial lactation (IL) in which the lame occurred in LG or not in the CG and in their corresponding subsequent later lactation (LL). For the analysis a generalized mixed linear model, the chi-square test and Odds Ratio (OR) were used. Differences were found respectively in IL (p<0.0018) and LL (p<0.0017) in L/305 production between the LG (10939.3 and 10479.6 l) and CG (11542.8 and 11110.9 l). Regarding TL, in IL there were no significant differences (p<0.16), but in LL the TL was higher (p<0.001) in CG cows than in LG. In the IL, the OD, IN and CI of the LG exceeded (p<0.0001) those of the CG, but no differences were found in LL. During the IL, infertility problems (p<0.0001) and genital tract infections (p<0.007) were higher in the LG. In the LL, the number of lame cows (45.4%) was higher (p<0.0001) in the LG group than those of CG (9.26%). In the IL and LL, a greater number of cows (p<0.0001) in the LG had a higher probability of being culled or dead than those in the CG, IL: OR= 7.51, CI 4.7-11.8 and LL: OR= 5.82; CI 3.28 -10.3. The present study shows the damage caused by lameness to productive, reproductive and health indices of central Argentina dairy farms.